Should we mind the gap? An assessment of the benefits of equity markets and policy implications for Europe's capital markets union - Benjamin Böninghausen; Johanne Evrard; Zakaria Gati; Sofia Gori; Claudia Lambert; Daniel Legran; Wagner Eduardo Schuster; Fons van Overbeek (European Central Bank (ECB), 2025)
The European Union (EU) economy depends heavily on bank funding. For this reason, strengthening EU equity markets as an alternative funding source has been a policy priority under the Capital Markets Union (CMU) agenda, and more recently a key feature of the Savings and Investment Union (SIU). EU listed equity markets are smaller and structurally different from those in the United States (US), with differing market capitalisations of listed firms and differences in the number of companies listed, stemming from lower initial public offering (IPO) activity in Europe. This paper aims to understand the drivers behind the EU-US listing gap, focusing on two aspects: (1) the general firm-level benefits of listing, and (2) whether pre-listing financing opportunities in the EU are underdeveloped, hindering firm growth and ultimately market depth. This paper first puts forward an empirical analysis on how a firm's decision to list impacts various key performance indicators, with a view to assessing the implications of listing for the economy at large. Second, it zooms in on innovative firms to shed light on the challenges faced by EU startups in their funding pipelines, with a focus on late-stage equity financing and venture capital (VC) markets. Focusing on the euro area (EA) as a proxy to derive broader benefits of listing in the EU, we find that EA companies' key profitability measures, employment, innovation capacity and productivity all increase after listing - and are thus indicative of wider economic benefits. This is, however, associated with challenges for the long-term investment strategies of listed companies, such as potential short-termism - a topic widely studied in the literature. Moreover, a comparison with the US suggests that, while the benefits and risks of listing are qualitatively similar on the other side of the Atlantic, EA companies seem to benefit somewhat less from listing than their US peers. Looking at pre-listing financing opportunities in the EU, the paper explores the interplay between VC and equity markets, suggesting that enhancing VC access and market size in Europe can support a vibrant pipeline of firms capable of listing domestically. Finally, acknowledging that there are multiple reasons for the listing gap between the EU and the US, and given our results on the impact of listing for EU firms, the paper offers policy recommendations to increase listings and improve pre-listing financing conditions by tackling long-standing obstacles in Europe's Single Market and the capital markets in particular.
Keywords: G10; G30; L10; L50 G24. G32; L21; L25; 330; single monetary policy; European Monetary System; euro area; monetary policy; single market; European Central Bank; Economic and Monetary Union; financial stability; Eurosystem; payment system; monetary integration; venture capital; savings and investments union; capital markets union; equity markets; listing; venture capital; financial structure